Teori Pemikiran Ekonomi Mikro Islam Perspektif Abu Ubaid dan Imam Al-Syaibani - Mutaqin, Kikin; Sulaeman, Sulaeman; Janwari, Yadi; Jubaedah, Dedah (JURNAL ECONOMINA, 2024)
Microeconomics is an economic science study that reviews individual behavior in conducting economic transactions. In the Islamic concept, microeconomics is characterized by the existence of norms that are applied within the limits of the Qur'an and Sunnah. The scholars of the classical period discussed many of these microeconomic issues, including Imam Abu Ubaid in his book al-Amwal and Imam al-Syaibani in his book al-kasb. This article explores the perspectives of these two influential men when examining microeconomic research through the use of descriptive qualitative methods and a review of relevant book and journal references. A Muslim scholar who specializes in Islamic economics is Imam Abu Ubaid whose ideas are contained in Kitab al-Amwal, one of the most influential scholarly references, containing many principles and concepts of public financial management. In addition to him, Iman As-Syaibani with his book Al-Kasb provides a view that work is human productivity that can make a person feel part of the world and has the value of worship for the pleasure of Allah SWT.